2020
DOI: 10.1111/ijfs.14615
|View full text |Cite
|
Sign up to set email alerts
|

Stability to thermal treatment of dipeptidyl peptidase‐IV inhibitory activity of a boarfish (Capros aper) protein hydrolysate when incorporated into tomato‐based products

Abstract: Biofunctional peptide ingredients should retain their stability following standard processing operations in food-based delivery vehicles. A boarfish protein hydrolysate, exhibiting anti-diabetic activity, was subjected to a range of thermal treatments following incorporation into tomato-based soup and juice products. The dipeptidyl peptidase-IV (DPP-IV) inhibitory activity and peptide profile of the hydrolysate within the products were assessed before and after thermal treatment. The treatments applied had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…You et al (2012) reported that loach peptide after heating at 121°C for 15 min showed higher radical-scavenging activity and Cu 2+ -chelating activity than after heating at 63°C for 30 min and 100°C for 20 min. However, thermal treatments (90°C for 1 min and 121°C for 42 s) of tomato beverage fortified with a boarfish (Capros aper) protein hydrolysate did not affect dipeptidyl peptidase-IV inhibitory activity (Harnedy-Rothwell et al, 2021). According to Lai et al (2016), pasteurisation (65°C for 30 min) and sterilisation (121°C for 20 min) treatments had no effect on reducing power and hydroxyl radical-scavenging activity of walnut meal protein hydrolysate.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…You et al (2012) reported that loach peptide after heating at 121°C for 15 min showed higher radical-scavenging activity and Cu 2+ -chelating activity than after heating at 63°C for 30 min and 100°C for 20 min. However, thermal treatments (90°C for 1 min and 121°C for 42 s) of tomato beverage fortified with a boarfish (Capros aper) protein hydrolysate did not affect dipeptidyl peptidase-IV inhibitory activity (Harnedy-Rothwell et al, 2021). According to Lai et al (2016), pasteurisation (65°C for 30 min) and sterilisation (121°C for 20 min) treatments had no effect on reducing power and hydroxyl radical-scavenging activity of walnut meal protein hydrolysate.…”
Section: Introductionmentioning
confidence: 92%
“…References Harnedy-Rothwell et al (2021) The results presented that adding protein hydrolysate into tomato products by using pasteurisation and sterilisation did not change the DPP-IV inhibitory activity. In addition, heat techniques had acceptable consumption to extend the shelf life.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…However, Harnedy-Rothwell et al found that the DPP-4 inhibitory activity of a boarfish hydrolysates was not affected by heat treatment when prepared in a tomato-based product. [93] Despite this interesting confliction between these two research groups, many others have shown more promising effects. A marine collagen peptide fraction administered to T2DM subjects showed marked improvements in fasting blood glucose, HbA 1c , and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to investigate the influence of coexisting food components on the absorption of food-derived peptides. Harnedy-Rothwell et al [187] subjected DPP-IV inhibitory peptides to simulated digestion in different matrices (tomato soup and juice), and verified that bioactivity was conserved. Different food matrices influenced protein and peptide digestibility during gastrointestinal digestion and absorption, so this must be considered a major factor in characterizing the bioaccessibility and bioavailability of peptides [174,188].…”
Section: Bioavailability In Vitromentioning
confidence: 98%
“…Guyomarc'h et al [216] reported the occurrence of the Maillard reaction within refrigerator-stored milk powder at 4 • C, whereas Albalá-Hutado et al [217] reported it in liquid infant's milk at room temperature. Recently, Harnedy-Rothwell et al [187] fortified different food products (tomato-based soup and juice products) that were subjected to thermal treatments (sterilization and pasteurization) and stored at refrigerated temperature for 30 days. No modification of bioactivity was reported, indicating this treatment's potential use on foods that could contain the bioactive protein hydrolysates.…”
Section: Stability and Functionality In Food Matricesmentioning
confidence: 99%